Rupture of a medial striate artery aneurysm associated with spontaneous middle cerebral artery stenosis. Issue 5 (26th July 2017) - Mitsutake, Akihiko; Hideyama, Takuto; Totsuka, Ryo; Sato, Tatsuya; Katsumata, Junko; Seki, Tomonari; Maekawa, Risa; Ito, Shoichi; Kishida, Yukiko; Kure, Shigeo; Shiio, Yasushi
Abstract: A 77‐year‐old man presented with left basal ganglia hematoma. Magnetic resonance angiography showed severe stenosis of the left middle cerebral artery (MCA), which had already been detected 7 years earlier. He had been free of symptoms caused by the stenosis. The hematoma was found to be caused by a rupture of a medial striate artery aneurysm. We suspected that this aneurysm formation was associated with the MCA stenosis, and that the underlying mechanism of MCA stenosis was similar to that of moyamoya disease. A genetic analysis of a variant in RING finger protein 213, a susceptibility gene for moyamoya disease, was negative, but other variants might be responsible for the MCA stenosis.